Facial hemangiossarcoma in a blue-fronted amazon parrot (Amazona aestiva) - Marietto-Gonçalves, Guilherme Augusto [UNESP] (2013)
Here we describe the first case report of an hemangiosarcoma in a male Blue-fronted amazon parrot (Amazona aestiva). The mass was localized near the inferior portion of the right orbit. A fine needle aspiration biopsy (FNAB) was performed and a presuntive diagnosis of hemangioma/hemangiosarcoma was established. Further histopathological evaluation revealed a mesenchymal neoplasm composed basically by well formed vascular channels lined by pleomorphic endothelial cells. Thus, the final diagnosis was a well-differentiated cutaneous hemangiosarcoma.